THU0499 IS THERE A DIFFERENT PRESENTATION OF JUVENILE SYSTEMIC DIFFUSE AND LIMITED SUBSET? DATA FROM THE JUVENILE SCLERODERMA INCEPTION COHORT. WWW.JUVENILE-SCLEORDERMA.COM. (2nd June 2020) - Foeldvari, I.; Klotsche, J.; Kasapcopur, O.; Adrovic, A.; Torok, K.; Terreri, M. T.; Sakamoto, A. P.; Stanevicha, V.; Sztajnbok, F. R.; Anton, J.; Feldman, B.; Alexeeva, E.; et al.
Abstract : Background: Juvenile systemic scleroderma (jSSc) is an orphan disease with a prevalence of 3 per 1 000 000 children. There are limited data regarding the clinical presentation of jSSc. The Juvenile Systemic Scleroderma Inception Cohort (JSSIC) is the largest multinational registry that prospectively collects information about jSSc patients. Objectives: Evaluation of the jSSc patients at the time of inclusion in the JSSIC. Methods: Patients were included in the JSSIC if they fulfilled the adult ACR/EULAR classification criteria for systemic scleroderma, if they presented the first non-Raynaud symptom before 16 years of age and if they were younger than 18 years of age at time of inclusion. Patients' characteristics at time of inclusion were evaluated. Results: Until 15 th of December 2019 hundred fifty patients were included, 83% of them being Caucasian and 80% female. The majority had the diffuse subtype (72%) and 17% of all jSSc had overlap features. The mean age of first presentation of Raynaud´s phenomenon was 9.8 years in the diffuse subtype (djSSc) and 10.7 years in the limited subtype (ljSSc) (p=.197). The mean age at first non-Raynaud's symptoms was 10.0 years in the djSSc and 11.2 years in the ljSSc (p=0.247). Mean disease duration at time of inclusion was 3.4 years in the djSSc and 2.4 years in the ljSSc group. Significant differences were found between the groups regarding mean modified Rodnan skin score, 18.2 in the djSSc vs 6.2 in the ljSSc (p=0.02); presence of Gottron´s papulae (djSSc 30% vs ljSSc 13%, p=0.43);presence of teleangiectasia (djSSc 42% vs 18% ljSS, p=0.01); history of ulceration (djSSc 42% vs 18% ljSSc, p=0.008); 6 Minute walk test below the 10 th percentile (djSSc 85% vs ljSSc 54%, p=0.044), total pulmonary involvement (djSSc 49% vs ljSSc 31%, p=0.045), cardiac involvement (ljSSc 17% vs djSSc 3%, p=0.002). djSSc patients had significantly worse scores for Physician Global Assessment of disease activity compared to ljSSc patients (VAS 0-100) (40 vs 15) (p=0.001) and for Physician Global Assessment of disease damage (VAS 0-100) (36 vs 17) (p=0.001). There were no statistically significant differences in the other presentations. Pulmonary hypertension occurred in approximately 6% in both groups. No systemic hypertension or renal crisis was reported. ANA positivity was 90% in both groups. Anti-Scl70 was positive in 35% in djSSc and 36% in the ljSSc group. Anticentromere positivity occurred in 3% in the djSSc and 7% in the ljSSc group. Conclusion: In this unique large cohort of jSSc patients there were significant differences between djSSc and ljSSc patients at time of inclusion into the cohort regarding skin, vascular, pulmonary and cardiac involvement. According to the physician global scores the djSSc patients had a significantly more severe disease. Interestingly the antibody profile was similar in both scleroderma phenotypes. Supported by the "Joachim Herz Stiftung" Disclosure of Interests: Ivan Foeldvari Consultant of: Novartis, Jens Klotsche: None declared, Ozgur Kasapcopur: None declared, Amra Adrovic: None declared, Kathryn Torok: None declared, Maria T. Terreri: None declared, Ana Paula Sakamoto: None declared, Valda Stanevicha: None declared, Flávio R. Sztajnbok: None declared, Jordi Anton Grant/research support from: grants from Pfizer, abbvie, Novartis, Sobi. Gebro, Roche, Novimmune, Sanofi, Lilly, Amgen, Grant/research support from: Pfizer, abbvie, Novartis, Sobi. Gebro, Roche, Novimmune, Sanofi, Lilly, Amgen, Consultant of: Novartis, Sobi, Pfizer, abbvie, Consultant of: Novartis, Sobi, Pfizer, abbvie, Speakers bureau: abbvie, Pfizer, Roche, Novartis, Sobi, Gebro, Speakers bureau: abbvie, Pfizer, Roche, Novartis, Sobi, Gebro, Brian Feldman Consultant of: DSMB for Pfizer, OPTUM and AB2-Bio, Ekaterina Alexeeva Grant/research support from: Roche, Pfizer, Centocor, Novartis, Speakers bureau: Roche, Novartis, Pfizer., Maria Katsikas: None declared, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl, edoardo marrani: None declared, Mikhail Kostik: None declared, Natalia Vasquez-Canizares: None declared, Simone Appenzeller: None declared, Mahesh Janarthanan: None declared, Monika Moll: None declared, Dana Nemcova: None declared, Anjali Patwardhan: None declared, Maria Jose Santos Speakers bureau: Novartis and Pfizer, Sujata Sawhney: None declared, Dieneke Schonenberg: None declared, Cristina Battagliotti: None declared, Lillemor Berntson Consultant of: paid by Abbvie as a consultant, Speakers bureau: paid by Abbvie for giving speaches about JIA, Blanca Bica: None declared, Juergen Brunner Grant/research support from: Pfizer, Novartis, Consultant of: Pfizer, Novartis, Abbvie, Roche, BMS, Speakers bureau: Pfizer, Novartis, Abbvie, Roche, BMS, Patricia Costa Reis: None declared, Despina Eleftheriou: None declared, Liora Harel: None declared, Gerd Horneff Grant/research support from: AbbVie, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Speakers bureau: AbbVie, Bayer, Chugai, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Daniela Kaiser: None declared, Dragana Lazarevic: None declared, Kirsten Minden Consultant of: GlaxoSmithKline, Sanofi, Speakers bureau: Roche, Susan Nielsen: None declared, Farzana Nuruzzaman: None declared, Yosef Uziel: None declared, Nicola Helmus: None declared